Predictors of voiding dysfunction following Uphold™ mesh repair for the treatment of pelvic organ prolapse. (December 2020) - Loo, Zi-Xi; Chen, Hung-Sheng; Tang, Feng-Hsiang; Lin, Kun- Ling; Liu, Yi-Yin; Wu, Ming- Ping; Long, Cheng-Yu
Abstract: Objective: To identify factors associated with voiding dysfunction after Uphold™ transvaginal mesh (TVM) repair in women with pelvic organ prolapse (POP). Study Design: We performed a retrospective analysis of 110 women with symptomatic pelvic organ prolapse (POP), anterior vaginal wall prolapse and/or apical prolapse (stage II to IV) who were scheduled for Uphold™ mesh surgery from September 2015 through December 2016. All subjects underwent urinalyses, UDI-6, IIQ-7, ICI-Q, POPDI-6, and pelvic examinations using the POP quantification (POP-Q) staging system before and after surgeries, with follow-up durations ranging from 24−36 months. Results: A total of 12 (10.9 %) of 110 women reported voiding dysfunction after Uphold™ mesh surgery. Using univariate analysis, there were no differences in body mass index and urodynamic parameters between normal voiding group and dysfunctional voiding group (P > 0.05). However, in patients aged above 71, POPDI-6 score≧13, preoperative concomitant urinary hesitancy, and incomplete emptying were found to be significant predictors of voiding dysfunction following Uphold™ mesh surgeries (P < 0.05). Conclusion: In patients aged above 71, POPDI-6 score≧13, preoperative concomitant urinary hesitancy, and incomplete emptying were significant predictors of voiding dysfunction after Uphold™.